(untitled) (Società e diritti, 2023)
The research theme of this work pertains to solidarity. Solidarity plays an important role in managing problems such as the covid-19 pandemic, the problem of refugees and that of migration. Non-profit organizations have an important role in making up for the shortcomings of the State and local authorities. Solidarity is the basis of non-profit organizations. This paper aims to enhance the theme of solidarity as a key to interpreting associations that are not temporary but can play an important role in achieving social well-being for the entire community.